Conceptualising the therapeutic alliance: exploring the relevance of Bordin's model for adults with intellectual disabilities. Issue 5 (6th August 2020) - Cameron, Sarah; Swanton, James; Dagnan, Dave
Abstract : Purpose: This study aims to explore the applicability of Bordin's model of therapeutic alliance in talking therapies for people with intellectual disabilities. Design/methodology/approach: People with intellectual disabilities and therapists in six therapy dyads were interviewed using a qualitative methodology. Data were analysed using thematic analysis to explore how people with learning disabilities constructed the dimensions of therapeutic alliance. Content analysis was then used to focus on therapy bond, therapy tasks and goals to explore the agreement on these dimensions between the therapist and client. Findings: People with intellectual disabilities reported their experience of therapy in a way that initially validates the alliance dimensions of Bordin's model. There was clear overlap within most dyads in the description of the characteristics of the bond, the tasks undertaken and the goals of therapy. Some therapists described additional goals based on their therapeutic model that were not clearly described by the client working with them. Research limitations/implications: This study is limited by only including six therapy dyads; however, the results suggest further research on the impact of therapy alliance and how goals and tasks are agreed would be valuable. Originality/value: Very few studies have explicitly examined the client's view of therapy alliance.